Minimalism : history, fashion, design, architecture, interiors - Cheviakoff, Sofi'a (Konemann, 2006)
"This book looks at all the disciplines influenced by the minimalism movement. It explains what minimal art is, how it developed in 1960s New York, and how a creative sensibility, which lasted for 40 years, was developed" -- Introduction